2023
DOI: 10.1007/s10811-023-02984-3
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Gongolaria barbata (Fucales, Phaeophyceae) with a seaweed-derived biostimulant in order to improve photophysiological fitness and promote fertility to advance the restoration of marine macroalgal forests

Abstract: As a result of several anthropogenic factors, Cystoseira sensu lato forests have declined or become regionally extinct in many coastal regions of the Mediterranean. Given the low natural recovery of lost populations, research efforts have been encouraged to develop sustainable and efficient restoration of macroalgal forests on a large scale. By promoting growth and fertility of collected thallus branches under controlled laboratory conditions, the availability of seedlings for restoration could be ensured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 94 publications
1
1
0
Order By: Relevance
“…A recent study on the cultivation of G. barbata even reported that, for thalli collected in the Gulf of Trieste, the development of fertile receptacles followed by the zygote release occurred exclusively at 14 • C [91]. Our experiments have shown that a temperature of 18 • C is still suitable for normal germlings' development, but germlings at 15 • C developed faster and reached larger lengths than others (see Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…A recent study on the cultivation of G. barbata even reported that, for thalli collected in the Gulf of Trieste, the development of fertile receptacles followed by the zygote release occurred exclusively at 14 • C [91]. Our experiments have shown that a temperature of 18 • C is still suitable for normal germlings' development, but germlings at 15 • C developed faster and reached larger lengths than others (see Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 43%
“…Gongolaria barbata is a geographically widespread species that belongs to the warmtemperate Mediterranean-Atlantic group [59,63] that requires temperatures of at least 10 °C for reproduction and development of germlings. It is a monoecious species, with oogonia and antheridia that are fertile in the conceptacles from the end of winter to the end of spring [91]. After the fertili ation, heavy and large ygotes exhibit highly restricted dispersal; therefore, they fall on the substrate a few centimeters to meters away from the The percentage of deformed germlings was highest at 24 and 28 • C, 1-2 days before the critical point at which all germlings died (Figures 3 and 5).…”
Section: Discussionmentioning
confidence: 99%